The Use of Lisdexamfetamine to Treat ADHD in a Patient with Stimulant (Methamphetamine) Use Disorder - Levine, J.; Swanson, H. (Case Reports in Psychiatry, 2023)
Introduction. The treatment of attention deficit hyperactivity disorder (ADHD) with stimulants among patients with stimulant use disorder carries concern for efficacy and exacerbation of addictive behaviors. Lisdexamfetamine is a unique stimulant used to treat ADHD with a lower abuse potential compared to other stimulants, as the medication is the only prodrug in its class. To our knowledge, there are no reports in the literature of the use of lisdexamfetamine to treat ADHD in patients with stimulant use disorder. Methods. We present a 33-year-old male with a history of stimulant (methamphetamine) use disorder, who was found to have long-standing ADHD. The patient was treated with lisdexamfetamine 30 mg, which was increased and sustained at 40 mg. Results. The patient reported significant improvement in focus, concentration, calmness, organization of thoughts, and less of a tendency to procrastinate. Additionally, he denied exacerbation of anxiety or sleep disturbances. He reported his cravings for stimulants were significantly decreased. After 2 months of treatment, he had moved out from his sober living facility, started a new job, and gained a promotion. He had no use of illicit substances, which was proven by routine urine drug screens. Conclusion. Our patient’s ADHD was successfully treated with lisdexamfetamine. Not only did the patient’s ADHD symptoms improve, but his cravings for stimulants were relieved. ADHD is common among patients with stimulant use disorder. Patients with ADHD and stimulant use disorder should not necessarily forgo pharmacologic treatment with stimulants for concerns of abuse. Due to its unique pharmacokinetic profile, lisdexamfetamine is a feasible treatment for patients with ADHD and a history of stimulant use disorder.